Lignin conversion into C4 dicarboxylic acids by catalytic wet peroxide oxidation using titanium silicalite-1 - Vega-Aguilar, Carlos A. (2021)
Lignin valorisation towards added-value products has become a relevant topic to consolidate a future circular bioeconomy. In this context lignin oxidation to C4 dicarboxylic acids (C4-DCA) by catalytic wet peroxide oxidation is emerging as a value-added strategy, supported by the extensive use of these building blocks in several industrial fields. In this work, lignins from different sources and processes (Indulin AT, Lignol, alkali and E. globulus kraft lignins) were oxidised using H2O2 and titanium silicalite-1 catalyst (TS-1) under different operating conditions (temperature, pH, time, H2O2, and TS-1 load). Indulin AT was the lignin leading to the highest succinic acid yield (11.3 wt%), and TS-1 catalyst enhanced its production four times over the noncatalysed reaction. Malic acid was also produced at high yields, especially for Lignol lignin. The other lignins (E. globulus kraft, and alkali lignins) also produced these C4 acids but at lower yields. The catalyst remained stable at the used experimental conditions, and showed potential to be reused for several cycles without being deactivated. Overall, the catalytic conversion of lignin to C4-DCA can help to guide the pathway to renewable chemicals production.